The Influence of Human Resource Quality and Work-Life Balance on Employee Performance with Job Satisfaction as a Moderating Variable at BPJS Ketenagakerjaan Branch Offices in Medan Raya - Delima Rumahorbo, Juliani; Farida Ferine, Kiki (PT. Multidisciplinary Press Indonesia, 2024)
This research aims to see the direct and indirect influence between the variables of human resource quality, work-life balance, performance and job satisfaction. This type of research uses quantitative, this research was conducted at BPJS Employment Branch Offices throughout Medan Raya. The population of this study was 132 employees and the sample used was the entire population using a saturated sampling technique. The data source used is a primary data source and data collection was carried out by distributing questionnaires. The research model used is phat analysis with smart PLS version 3.3.3. as a research measuring tool. The results of this research are that the Quality of Human Resources has a positive and significant effect on Employee Performance with an original sample value of 0.593 and a P value of 0.000. This means that the quality of human resources has a positive influence on the company and the quality of human resources influences the company's performance significantly. Work-life balance has a positive and insignificant effect on employee performance with an original sample value of 0.041 and a p value of 0.698. This means that Work Life Balance is not able to improve employee performance for the company. Job Satisfaction has a positive and significant effect on Employee Performance with an original sample value of 0.590 and a P value of 0.000 Job Satisfaction is able to moderate the influence of Human Resource Quality on Employee Performance indirectly with the original sample result being 0.277 and p value 0.013. This means that job satisfaction is an intervening variable because it can influence HR quality on employee performance indirectly. Job Satisfaction is able to moderate the influence of Human Resource Quality on Employee Performance indirectly with an original sample value of 0.159 and a p value of 0.168. This means that job satisfaction is an intervening variable that is unable to influence Work Life Balance on employee performance indirectly.